Hubungan Pengetahuan Kewarganegaraan Tentang Norma Dengan Sikap Patuh Terhadap Norma - Prasetyo, Ardhin; Wijianto, Wijianto; Muchtarom, Muchtarom (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2023)
AbstractThis study aims to prove whether there is a relationship between knowledge of norms and adherence to norms in class VII students of SMPN 8 Surakarta. This research uses quantitative methods with correlational quantitative research types. The variables in this study are knowledge of norms and adherence to norms. The population of this study were all class VII students of SMPN 8 Surakarta, totaling 254 students. The sample in this study was 60 students in classes VII D and VII H. The sampling technique was Cluster Random Sampling. The validity test used the Biserial Point test and the Product Moment test. The reliability test used the Spearman-Brown test and the Cronbach Alpha test. Test the hypothesis using the Spearman rank test and look for the regression equation. The results of this study, there is a value of Sig. that is 0.00 and R that is 0.413. From these values, is that students who have knowledge of high norms, these students will also have an obedient attitude toward high norms as well. These results reinforce the theory of Stimulus Organism Response and Cognitive Affective Consistency. The process of the occurrence of a relationship is described through the Elaboration Likelihood Model. and The Assimilation-Contrast theory.——–AbstrakPenelitian ini bertujuan untuk membuktikan apakah terdapat hubungan pengetahuan tentang norma dengan sikap patuh terhadap norma pada siswa kelas VII SMPN 8 Surakarta. Penelitian ini menggunakan metode kuantitatif dengan jenis kuantitatif korelasional. Variabel dalam penelitian ini yaitu pengetahuan tentang norma dan sikap patuh terhadap norma. Populasi dari penelitian ini yaitu siswa kelas VII SMPN 8 Surakarta yang berjumlah 254 siswa. Sampel dalam penelitian ini yaitu 60 siswa kelas VII D dan VII H. Teknik pengambilan sampel yaitu Cluster Random Sampling. UJi validitas menggunakan uji Point Biserial dan uji Product Moment. Uji reliabilitas menggunakan uji Spearman Brown dan uji Cronbach Alpha. Uji hipotesis melalui uji Spearman Rank serta dicari persamaan regresi. Hal penelitian yaitu terdapat nilai Sig. yaitu 0,00 dan R yaitu 0,413. Nilai tersebut menunjukan bahwa siswa yang memiliki pengetahuan tentang norma tinggi, maka siswa tersebut juga akan memiliki sikap patuh terhadap norma yang tinggi juga. Hasil tersebut memperkuat teori Stimulus Organisme Respons dan Cognitive Affective Consistency. Proses hubungan dijelaskan melalui Elaboration Likelihood Model dan The Assimilation-Contrast theory.